2007
DOI: 10.1002/hep.21757
|View full text |Cite
|
Sign up to set email alerts
|

Clinical progression of hepatitis C virus-related chronic liver disease in human immunodeficiency virus-infected patients undergoing highly active antiretroviral therapy

Abstract: Little is known about the natural history of liver disease in human immunodeficiency virus (HIV)/hepatitis C virus (HCV)-coinfected subjects under highly active antiretroviral therapy (HAART). The objectives of this study were to obtain information about the mortality, the incidence of hepatic decompensations, and the predictors thereof in this population. In a multicenter cohort study, the time to the first hepatic decompensation and the survival of 1,011 antiretroviral naïve, HIV/HCV-coinfected patients who … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
117
1
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
3
2

Relationship

1
4

Authors

Journals

citations
Cited by 175 publications
(137 citation statements)
references
References 29 publications
15
117
1
4
Order By: Relevance
“…25 The impact of immunosuppression on liver mortality is one reason for this recommendation. [2][3][4][5] In the present study, lack of control of HIV replication was a risk factor for progression. This is an additional reason to consider earlier ART initiation.…”
Section: Discussionmentioning
confidence: 49%
See 4 more Smart Citations
“…25 The impact of immunosuppression on liver mortality is one reason for this recommendation. [2][3][4][5] In the present study, lack of control of HIV replication was a risk factor for progression. This is an additional reason to consider earlier ART initiation.…”
Section: Discussionmentioning
confidence: 49%
“…[12][13][14] On the contrary, in a prospective cohort of ART-naïve patients, HAART-mediated control of HIV RNA was a protective factor for liver-related death. 5 We found that fibrosis progression between liver biopsies was independently related with HIV RNA suppression both in the global study group and in the patients without anti-HCV treatment. A possible mechanism underlying the association of HIV suppression and fibrosis progression is the effect of HIV on fibrogenesis.…”
Section: Discussionmentioning
confidence: 67%
See 3 more Smart Citations